User interface design and evaluation (Morgan Kaufmann, 2005)
"User Interface Design and Evaluation is comprehensive and clear. It's an amazing achievement - a textbook in plain English that works both for the classroom and for practitioners learning on their own. It covers the entire user-centered design process with details on the steps and techniques for requirements gathering, design, and evaluation. It includes great stories and case studies as well as engaging exercises. This is a superb book that puts all the pieces together." - Ginny Redish, Redish & Associates, Inc.